2019
DOI: 10.2147/dddt.s187842
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low-dose doxycycline inhibits hydrogen peroxide-induced oxidative stress, MMP-2 up-regulation and contractile dysfunction in human saphenous vein grafts</p>

Abstract: Background: Cardiopulmonary bypass (CPB) applied during coronary artery bypass grafting (CABG), promotes inflammation, generation of reactive oxygen species (ROS) and up-regulation of matrix metalloproteinases (MMPs). All these complications may lead to contractile dysfunction, restenosis and early graft failure, restricting long-term efficacy of bypass grafts. Low-dose doxycycline is a potent MMP inhibitor and ROS scavenger. In this study, we aimed to investigate the effects of doxycycline on ROS g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Along these lines, the reversal of CS-induced emphysema and PH by riociguat treatment in mice was associated with decreased MMP activity and expression (4). It has been shown that doxycycline not only inhibited MMP activity but also decreased MMP expression (27,31,50). In our current study, doxycycline decreased MMP-2 and MMP-9 expression on the protein level in the lung homogenates from mice that were exposed to CS.…”
Section: Discussionsupporting
confidence: 59%
“…Along these lines, the reversal of CS-induced emphysema and PH by riociguat treatment in mice was associated with decreased MMP activity and expression (4). It has been shown that doxycycline not only inhibited MMP activity but also decreased MMP expression (27,31,50). In our current study, doxycycline decreased MMP-2 and MMP-9 expression on the protein level in the lung homogenates from mice that were exposed to CS.…”
Section: Discussionsupporting
confidence: 59%
“…Treatment with 100 µM H 2 O 2 did not affect vasoconstriction in response to 1 µM phenylephrine in the TEBVs (Figure 3A,C). In contrast, human saphenous vein samples showed a reduction in vasoconstriction ex vivo when treated with as little as 10 µM H 2 O 2 for 16 h [32]. It is important to note that these data were obtained using a much higher concentration of noradrenaline (100 µM) as a vasoconstrictor, rather than the low dose of phenylephrine (1 µM) used here.…”
Section: Discussionmentioning
confidence: 69%
“…Other reports demonstrated that high wall-shear stress and cyclic shear stress increase the expression of Angiopoietin-2 and its receptor Tie2, which leads to activation of the PI3K/Akt pathway. This results in the expression of eNOS and the subsequent increase in the released NO from ECs [87,88].…”
Section: Endothelial Lining Formationmentioning
confidence: 99%